The First-Principle Study on Tuning Optical Properties of MA2Z4 by Cr Replacement of Mo Atoms in MoSi2N4 - Yongsheng Li; Jiawei Li; Lingyu Wan; Jiayu Li; Hang Qu; Cui Ding; Mingyang Li; Dan Yu; Kaidi Fan; Huilu Yao (Nanomaterials, 2022)
Recently, with the successful preparation of MoSi2N4, an emerging family of two-dimensional (2D) layered materials has been predicted with a general formula of MA2Z4 (M: an early transition metal, A: Si or Ge and Z: N, P, or As). In terms of this new type of 2D material, how to effectively tune its light absorption properties is unclear. We systematically discuss the effects of replacing Mo with Cr atoms on the lattice structure, energy bands, and light absorption properties of 2D monolayer MoSi2N4 using density functional theory (DFT) and the Vienna Ab initio Simulation Package (VASP). Additionally, the results show that the single replacement of the atom Cr has no significant effect on the lattice structure of the outermost and sub-outer layers but plays a major role in the accumulation of electrons. In addition, the 2D MoSi2N4, Mo0.5Cr0.5Si2N4, and CrSi2N4 all have effective electron–hole separation properties. In the visible region, as the excited state increases, the required excitation energy is higher and the corresponding wavelength of light is shorter. It was found that the ultraviolet (UV)–visible spectra are red-shifted when Cr atoms replace Mo atoms in MoSi2N4; when Cr atoms and Mo atoms coexist, the coupling between Cr atoms and Mo atoms achieves modulation of the ultraviolet (UV)–visible spectra. Finally, we reveal that doping M-site atoms can effectively tune the light absorption properties of MA2Z4 materials. These results provide a strategy for the design of new 2D materials with high absorption properties.